1995
DOI: 10.1056/nejm199501263320402
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Subjects with Long-Term Nonprogressive Human Immunodeficiency Virus Infection

Abstract: In persons who remain free of disease for many years despite HIV infection the viral load is low, but viral replication persists. Lymph-node architecture and immune function appear to remain intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
296
1
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 672 publications
(318 citation statements)
references
References 31 publications
14
296
1
2
Order By: Relevance
“…Recent data on LTNP indicate that they have low levels of HIV-1 in the presence of strong virus-specific immune responses, combined with some degree of viral attenuation (Cao et al, 1995). Similar observations concerning low plasma levels of HIV-1 RNA and viral burden in PBMC from LTNP have been reported by Pantaleo et al, who also showed that lymph-node architecture and immune function appear to remain intact in these subjects (Pantaleo et al, 1995). Accordingly, the main aims of this study were the following: (i) to ascertain whether PBMC from LTNP have a different tendency to undergo apoptosis either spontaneously or after treatment with a mitogen (pokeweed mitogen, PWM), or with anti-CD95 monoclonal antibodies, in comparison with cells from subjects who show signs of progression of the infection (HIV+P) and from seronegative controls; (ii) to identify the phenotype of apoptotic cells, in order to see whether in LTNP different lymphocyte subsets have a different propensity to cell death; (iii) to ascertain whether spontaneous or induced apoptosis can be modulated by agents such as growth factors (interleukin-2, IL-2), molecules able to inhibit poly(ADPribosyl)polymerase (nicotinamide, NAM; 3-aminobenzamide, 3-ABA), or to increase intracellular reduced glutathione (GSH) content (N-acetyl-L-cysteine, NAC) or energy charge (L-acetyl-carnitine, LAC).…”
Section: Introductionsupporting
confidence: 68%
“…Recent data on LTNP indicate that they have low levels of HIV-1 in the presence of strong virus-specific immune responses, combined with some degree of viral attenuation (Cao et al, 1995). Similar observations concerning low plasma levels of HIV-1 RNA and viral burden in PBMC from LTNP have been reported by Pantaleo et al, who also showed that lymph-node architecture and immune function appear to remain intact in these subjects (Pantaleo et al, 1995). Accordingly, the main aims of this study were the following: (i) to ascertain whether PBMC from LTNP have a different tendency to undergo apoptosis either spontaneously or after treatment with a mitogen (pokeweed mitogen, PWM), or with anti-CD95 monoclonal antibodies, in comparison with cells from subjects who show signs of progression of the infection (HIV+P) and from seronegative controls; (ii) to identify the phenotype of apoptotic cells, in order to see whether in LTNP different lymphocyte subsets have a different propensity to cell death; (iii) to ascertain whether spontaneous or induced apoptosis can be modulated by agents such as growth factors (interleukin-2, IL-2), molecules able to inhibit poly(ADPribosyl)polymerase (nicotinamide, NAM; 3-aminobenzamide, 3-ABA), or to increase intracellular reduced glutathione (GSH) content (N-acetyl-L-cysteine, NAC) or energy charge (L-acetyl-carnitine, LAC).…”
Section: Introductionsupporting
confidence: 68%
“…This population of children probably included a highly selected group of patients who had minimal to no progression of HIV disease such as the cohort of adult nonprogressors described in recent studies. 16,17 All patients in the survey were long-term survivors based exclusively on their age. However, it is apparent that long-term survivors constitute a diverse patient population within the dynamic process of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ultimate reasons for that especially favourable behaviour of an otherwise fatal disease are not clear at the moment, some important points have been recently addressed. These subjects are characterized by very low levels of viral burden in the plasma, by a strong neutralizing antibody response, and by vigorous inhibitory CD8 lymphocytes [6,7].…”
Section: Introductionmentioning
confidence: 99%